A Qualitative Study of Self and Caregiver Perspectives on How Autistic Individuals Cope With Trauma - Ng-Cordell, Elise; Rai, Anika; Peracha, Hira; Garfield, Tamara; Lankenau, Stephen E.; Robins, Diana L.; Berkowitz, Steven J.; Newschaffer, Craig; Kerns, Connor M. (Frontiers in Psychiatry, 2022)
Background Coping can moderate the relationship between trauma exposure and trauma symptoms. There are many conceptualisations of coping in the general population, but limited research has considered how autistic individuals cope, despite their above-average rates of traumatic exposure. Objectives To describe the range of coping strategies autistic individuals use following traumatic events. Methods Fourteen autistic adults and 15 caregivers of autistic individuals, recruited via stratified purposive sampling, completed semi-structured interviews. Participants were asked to describe how they/their child attempted to cope with events they perceived as traumatic. Using an existing theoretical framework and reflexive thematic analysis, coping strategies were identified, described, and organized into themes. Results Coping strategies used by autistic individuals could be organized into 3 main themes: (1) Engaging with Trauma, (2) Disengaging from Trauma, and (3) Self-Regulatory Coping. After the three main themes were developed, a fourth integrative theme, Diagnostic Overshadowing, was created to capture participants' reports of the overlap or confusion between coping and autism-related behaviors. Conclusions Autistic individuals use many strategies to cope with trauma, many of which are traditionally recognized as coping, but some of which may be less easily recognized given their overlap with autism-related behaviors. Findings highlight considerations for conceptualizing coping in autism, including factors influencing how individuals cope with trauma, and how aspects of autism may shape or overlap with coping behavior. Research building on these findings may inform a more nuanced understanding of how autistic people respond to adversity, and how to support coping strategies that promote recovery from trauma.